Penerapan Motode Manhaj Dalam Meningkatkan Pemahaman Membaca Al-Quran di SMP Swasta Amir Hamzah Medan - Hasibuan, Marhan; Hidayat, Muhammad Arif (Yayasan Rahmat Islamiyah, 2024)
Manhaj method is a Quran learning method designed to facilitate the understanding of the Quran. The Manhaj Method of Learning the Quran at Amir Hamzah Junior High School Medan is related to Islamic education in grade 8. This service is promoted by Muslim teachers with the aim of improving learning habits in the classroom. This activity takes action in the form of applying the Manhaj method to a new teaching method. There are three objectives to be achieved by using the Manhajj method: material objectives, moral objectives, and structural objectives. This activity is very helpful especially for the younger generation to create a generation that loves the Quran and has strong faith, piety, and good character.